2011
DOI: 10.1159/000329524
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Suppression in Subjects with Perennial Allergic Rhinitis Treated with Mometasone Furoate Nasal Spray

Abstract: Background: Allergic rhinitis (AR) carries a high symptom burden and impact on quality of life. The ability of an AR treatment to achieve and sustain symptom suppression would be expected to enhance quality of life and improve long-term outcomes. Methods: In this ad hoc analysis of data from 4 phase 3 clinical trials of mometasone furoate nasal spray (MFNS), subjects with perennial AR recorded the severity of nasal symptoms twice daily for 12 weeks on a 4-point scale to determine the total nasal symptom score.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…1 Mometasone furoate nasal spray (MFNS) is an intranasal corticosteroid (INS) shown to be safe and efficacious for seasonal AR (SAR) and perennial AR (PAR). [2][3][4] Recent clinical trials established the ability of MFNS to significantly relieve SAR nasal symptoms, including congestion, for a full 24-hour dosing interval and to sustain relief over a 2-week treatment period. 2,5 Oxymetazoline (OXY) is an intranasal decongestant used to treat nasal congestion by activating ␣-adrenergic receptors, resulting in constriction of nasal blood vessels and, with rapid onset of action, improving airflow.…”
mentioning
confidence: 99%
“…1 Mometasone furoate nasal spray (MFNS) is an intranasal corticosteroid (INS) shown to be safe and efficacious for seasonal AR (SAR) and perennial AR (PAR). [2][3][4] Recent clinical trials established the ability of MFNS to significantly relieve SAR nasal symptoms, including congestion, for a full 24-hour dosing interval and to sustain relief over a 2-week treatment period. 2,5 Oxymetazoline (OXY) is an intranasal decongestant used to treat nasal congestion by activating ␣-adrenergic receptors, resulting in constriction of nasal blood vessels and, with rapid onset of action, improving airflow.…”
mentioning
confidence: 99%
“…5 Complications can occur in allergic rhinitis and they can significantly impair quality of life. [9][10][11][12][13] Published data on safety and cost effectiveness of intranasal corticosteroids support the use of intranasal corticosteroids over oral antihistamines as first line treatment for allergic rhinitis. 8 Corticosteroids are widely used for suppression of inflammation in allergic rhinitis as well as in other chronic inflammatory diseases.…”
mentioning
confidence: 99%
“…A survey results published in year 2011 reported that patients with allergic rhinitis were on about additional nine prescriptions than similar patients without allergic rhinitis, resulting in an incremental healthcare cost amounting to nearly 1,500 US $ per year . Corticosteroids are widely used for suppression of inflammation in allergic rhinitis as well as in other chronic inflammatory diseases . Published data on safety and cost effectiveness of intranasal corticosteroids support the use of intranasal corticosteroids over oral antihistamines as first line treatment for allergic rhinitis …”
mentioning
confidence: 99%